2005
DOI: 10.1124/dmd.105.004259
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Model for Predicting Human Hepatic, Metabolic Clearance From in Vitro Intrinsic Clearance Data in Hepatocytes and Microsomes

Abstract: ABSTRACT:The aim of this study was to evaluate a unified method for predicting human in vivo intrinsic clearance (CL int, in vivo ) and hepatic clearance (CL h ) from in vitro data in hepatocytes and microsomes by applying the unbound fraction in blood (fu b ) and in vitro incubations (fu inc ). Human CL int, in vivo was projected using in vitro data together with biological scaling factors and compared with the unbound intrinsic clearance (CL int, ub, in vivo ) estimated from clinical data using liver models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
292
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(315 citation statements)
references
References 25 publications
22
292
1
Order By: Relevance
“…Previous research has shown that the in vivo hepatic Cl can accurately be estimated from in vitro data in both microsomes and hepatocytes. 36 Nevertheless, hepatic uptake transporters have been shown to modulate Cl of compounds that is predominantly mediated by metabolic enzymes when measured in hepatocyte systems. 31 Therefore, the metabolic intrinsic Cl of HIV PI was measured in pooled liver microsomes (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the in vivo hepatic Cl can accurately be estimated from in vitro data in both microsomes and hepatocytes. 36 Nevertheless, hepatic uptake transporters have been shown to modulate Cl of compounds that is predominantly mediated by metabolic enzymes when measured in hepatocyte systems. 31 Therefore, the metabolic intrinsic Cl of HIV PI was measured in pooled liver microsomes (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…Additional input information for the well-stirred model such as f up , the B:P ratio and f umic were determined experimentally. If these were not available, the B:P ratio was assumed to be 1 (for compounds that are either neutral or basic, 0.55 may be assumed for acids [10]) and f umic and f up were calculated in Simcyp W [26]. The successful performance of IVIVE in preclinical species was used as a means to add confidence to human IVIVE.…”
Section: Prediction Of Clearancementioning
confidence: 99%
“…An important aspect of PBPK modeling for compounds cleared primarily by the liver is the application of IVIVE methods to predict in vivo clearance from in vitro metabolic data. The utility of IVIVE for hepatic metabolic clearance has been well established in the literature [8][9][10] and is developing to improve poor predictions by incorporating hepatic uptake and/or biliary excretion [11,12]. Briefly, the in vitro intrinsic clearance (CL int ) or enzyme kinetic data (K m and V max ) are scaled to an in vivo CL int by accounting for the microsomal protein content or hepatocellularity and liver weight.…”
Section: Introductionmentioning
confidence: 99%
“…The use of these scaling factors resulted in 15 to 30% lower CL hep values of PF02341066 and PF04217903. For consistency with previous reports (Obach et al, 1997;Obach 1999;Naritomi et al, 2003;Riley et al, 2005;Hosea et al, 2009), the scaling factors indicated above were used for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Although allometric scaling is an empirical approach, it has been widely used and provided reliable predictions for a number of highly metabolized and renally excreted drugs (Boxenbaum, 1984;Mordenti, 1986;Mahmood and Balian, 1996). Over the last two decades, the methods for extrapolating in vivo CL from in vitro data (i.e., IVIVE) have been applied extensively with the increased availability of human liver samples (e.g., microsomes, hepatocytes, liver slices, and others) and have demonstrated prediction accuracy for metabolic CL of low to high hepatic extraction compounds (Houston and Carlile, 1997;Obach et al, 1997;Obach, 1999;Riley et al, 2005;Shiran et al, 2006). In recent years, there has been growing interest in the physiologically based pharmacokinetic (PBPK) model, which provides the disposition profiles in various species to be predicted from physicobiochemical properties of compounds with the species-specific physiological parameters (Jones et al, 2006;De Buck et al, 2007;Lavé et al, 2007;Nestorov, 2007).…”
Section: Introductionmentioning
confidence: 99%